Unusual Complication of the Foramen Magnum Decompression - Narayana, Sridhara; Teegala, Ramesh (Nepal Journal of Neuroscience, 2019)
The pathophysiology of Chiari-Imalformation lies with the abnormal CSF flow across Foramen magnum and Foramen magnum decompression (FMD) restores this flow. However, recent data suggests that FMD itself can alter the CSF dynamics in an abnormal fashion resulting in raised intracranial pressure. We report such a case where FMD has led to the development of subdural hygroma and hydrocephalus. Patient was managed with VP shunt after a failed trial of re-exploration and burr hole drainage. The mechanism behind this complication is not clearly understood despite several hypotheses being proposed. Once established, management has to be individualized, based upon the clinical condition and location of CSF collection.